Neural correlates of heart rate variability in PTSD during sub‐ and supraliminal processing of trauma‐related cues. Issue 10 (17th July 2017) - Rabellino, Daniela; D'Andrea, Wendy; Siegle, Greg; Frewen, Paul A.; Minshew, Reese; Densmore, Maria; Neufeld, Richard W.; Théberge, Jean; McKinnon, Margaret C.; Lanius, Ruth A.
Abstract: Background: Posttraumatic stress disorder (PTSD) is characterized by dysregulated arousal and altered cardiac autonomic response as evidenced by decreased high‐frequency heart rate variability (HF‐HRV), an indirect measure of parasympathetic modulation of the heart. Indeed, subtle threatening cues can cause autonomic dysregulation, even without explicit awareness of the triggering stimulus. Accordingly, examining the neural underpinnings associated with HF‐HRV during both sub‐ and supraliminal exposure to trauma‐related cues is critical to an enhanced understanding of autonomic nervous system dysfunction in PTSD. Methods: We compared neural activity in brain regions associated with HF‐HRV in PTSD ( n  = 18) and healthy controls ( n  = 18) during exposure to sub‐ and supraliminal processing of personalized trauma‐related words. Results: As compared to controls, PTSD exhibited decreased HF‐HRV reactivity in response to sub‐ and supraliminal cues. Notably, during subliminal processing of trauma‐related versus neutral words, as compared to controls, PTSD showed decreased neural response associated with HF‐HRV within the left dorsal anterior insula. By contrast, during supraliminal processing of trauma‐related versus neutral words, decreased neural activity associated with HF‐HRV within the posterior insula/superior temporal cortex, and increased neural activity associated with HF‐HRV within the left centromedial amygdala was observed in PTSD as compared to controls. Conclusions: Impaired parasympathetic modulation of autonomic arousal in PTSD appears related to altered activation of cortical and subcortical regions involved in the central autonomic network. Interestingly, both sub‐ and supraliminal trauma‐related cues appear to elicit dysregulated arousal and may contribute to the maintenance of hyperarousal in PTSD. Hum Brain Mapp 38:4898–4907, 2017 . © 2017 Wiley Periodicals, Inc.